Towards a remote animal tagging method with minimal detriment; how do animals react to new constructions in their environment? - VICTORIA THOMAS (2024)
Tags that researchers attach to animals are equipped with a variety of sensory systems which allow us to quantify the ultra-fine scale movement of animals. Such technology aids conservation efforts by providing evidence-based data on the causal drivers behind animal space use. Yet, the attachment of tags sometimes requires individuals to be captured or restrained, which can cause acute stress and unusual movement patterns. To circumvent these issues, we are developing a remote tagging apparatus (TA), consisting of a gateway which deploys a tag when an animal walks underneath. A first step in investigating the feasibility of this tagging system in the wild is to investigate how animals react to a TA in their environment. Here, I deployed TAs at 22 field sites around Swansea, South Wales, and monitored the reactions of animals to them using camera traps. I focused on terrestrial carnivores (particularly foxes (Vulpes vulpes), otters (Lutra lutra) and badgers (Meles meles), but also recorded the reactions of other mammals and birds to the gateways. I aimed to examine (1) how animals react to the gateway, (2) whether animals showed neophobia to the gateway, and if this decreased over time, (3) how the siting of the gateway influenced whether animals were more likely to walk under it, and (4) whether baiting around the gateway increased the number of individuals that visited the site. I demonstrate that animals initially show neophobia of the gateway, but this decreases over time. Habitat specifics (i.e. vegetation cover and the density of the animal path/trail) made no difference in the number of times animals walked under the gateway, whereas baiting the gateway significantly increased number of animals visiting the site. These findings imply that remote tagging is possible but neophobia must be taken into account. Whilst still in the developmental stage, this remote tagging project shows potential for future studies wishing to tag animals without capturing or restraining them.